Corporate Social Responsibility Initiatives for Promotion of Public Libraries - Vijay Kumar, P. (DESIDOC Journal of Library & Information Technology, 2013)
This article is intended to understand whether the corporate social responsibility initiatives of thecorporates are improving the state of public libraries. it also seeks to understand whether corporatestake initiatives proactively to promote public libraries, how the public and private sectors are lending theirsupport to the public library movement, what will be the way forward, and opportunities ahead to tap CSR resources for developing the public libraries. http://dx.doi.org/10.14429/djlit.33.1.3727